Toward a Sustainable Future: Islamic Education Strategies to Cultivate Moral and Ethical Muslim Youth at ICC Muar Johor, Malaysia - Anip Dwi Saputro; Devid Dwi Erwahyudin; Lasmi Lasmi; Sudarmadi Sudarmadi (Scientia Publica Media, 2025)
Moral education plays a vital role in shaping students’ character and personality, guiding them to become individuals with noble character, a strong sense of responsibility, and high social awareness. The Indonesian Community Center (ICC) Muar, located in Johor, Malaysia, serves as an educational institution for children of Indonesian migrant workers at the elementary level. It holds a significant responsibility in embedding moral values through effective and sustainable learning strategies tailored to the unique needs of its students. This study aims to explore the strategies employed in Islamic education at ICC Muar in fostering a morally grounded Muslim generation. A descriptive qualitative research design was adopted, utilizing observation, interviews, and documentation as the primary data collection techniques. The findings reveal that ICC Muar integrates several key strategies in its moral education efforts: modeling by teachers who serve as moral exemplars, active and participatory learning methods, the use of interactive learning media, and the incorporation of religious and social activities that emphasize direct practice and application. These strategies contribute not only to students’ increased religious understanding but also to the internalization of moral behaviors in daily life, such as discipline, empathy, and social responsibility. The learning approach at ICC Muar is deeply rooted in Islamic values, creating a holistic and supportive educational environment. As a result, the institution successfully nurtures a generation of students who are not only intellectually capable but also possess strong moral integrity and spiritual depth, aligning with the broader goals of Islamic moral education.